Epidermal growth factor receptor mutations in malignant pleural and peritoneal mesothelioma. Issue 6 (12th March 2012) - Enomoto, Yasunori; Kasai, Takahiko; Takeda, Maiko; Takano, Masato; Morita, Kohei; Kadota, Eiji; Iizuka, Norishige; Maruyama, Hiroshi; Haratake, Joji; Kojima, Yu; Ikeda, Naoya; Inatsugi, Naoki; et al.
Abstract : Background: Epidermal growth factor receptor (EGFR) gene mutation at the kinase domain and EGFR gene amplification are reported to be predictors of the response to EGFR tyrosine kinase inhibitors in lung cancer cases. In malignant mesothelioma (MM), the role of EGFR is less clear. Methods: Thirty-eight MM specimens were submitted to EGFR mutation evaluation, and compared with the results of immunohistochemical staining and fluorescence in situ hybridization (FISH) analysis. DNA was extracted from paraffin blocks and PCR was performed to amplify exon regions 18–21 of the EGFR gene. Direct sequencing of the purified PCR products was performed. Results: Five EGFR missense mutations were detected in six of the 38 patients (16%); two of these mutations were novel, two were originally detected in non-small cell lung carcinoma, and one resembled a location previously noted for malignant peritoneal mesothelioma. Conclusion: As far as the authors are aware there has been no report of the EGFR mutation of MM in Japanese cases, but in this study EGFR missense mutations were detected in some cases. EGFR mutation results were not related to immunohistochemical and FISH analysis.